Improving Poetry Writing Skills Through Image Media in Class 1 Students of SDN Suru Sunda 01 - Shoimatun Febriyani (Universitas Sebelas Maret, 2021)
This study aims to improve poetry writing skills in grade 1 students at SDN Suru Sunda 01 through the use of media images. The research method used was Classroom Action Research (PTK) involving 14 students as participants in the research. The research was conducted in 2 cycles with each cycle consisting of 3 stages, namely planning, action, and reflection.Data were collected through observation, tests, and interviews. The results showed that there was an increase in students' poetry writing skills after using picture media in learning. In the first cycle, the average student score increased from 63 to 74, then increased again in the second cycle to 83. In addition, the results of the interviews also showed that students were more motivated in writing poetry when using media images. It is hoped that the results of this study can contribute to teachers in improving poetry writing skills in grade 1 students at SDN Suru Sunda 01, as well as being a reference for other researchers who are interested in continuing research on the use of media in learning to write poetry.